Infección de vías urinarias asociada a amenaza de parto pretermino en pacientes atendidas en el Hospital General Martín Icaza, Babahoyo-Los Ríos, mayo-septiembre 2019. - Andrade Peña, Karen Rosalia (2019)
Urinary tract infections are one of the most frequent complications in pregnancy, during which there are functional and structural changes of the urinary tract that favor infection. Around 8 million women suffer these complications during pregnancy, with data with an estimated incidence of 5 to 10% of urinary infections worldwide. This pathology is one of the most frequent clinical entities during pregnancy and one of the main causes of demand for medical care in health centers in Ecuador, according to the National Institute of Statistics and Census, are in seventh place in relation to the ten main causes of general morbidity. The objective of this research project is to identify the type of Urinary Tract Infection Associated with Preterm Birth Threat in patients treated at the Martín Icaza General Hospital, Babahoyo-Los Ríos, May-September 2019. The types of research they used were descriptive, non-experimental, retrospective and cross-sectional that helped us obtain information on the variables and all kinds of information on urinary tract infections at the Martin Icaza General Hospital to use the techniques and instruments. Likewise, it was possible to demonstrate the result obtained throughout the investigation, concluding that urinary tract infections constitute one of the main causes of preterm birth threat, with cystitis being the most associated with this complication.